Adhesion molecule expression and function of primary endothelial cells in benign and malignant tissues correlates with proliferation - Sievert, Wolfgang; Tapio, Soile; Breuninger, Stephanie; Gaipl, Udo; Andratschke, Nicolaus; Trott, Klaus-Ruediger; Multhoff, Gabriele (PLoS ONE, 2014)
Comparative analysis of the cellular biology of the microvasculature in different tissues requires the availability of viable primary endothelial cells (ECs). This study describes a novel method to isolate primary ECs from healthy organs, repair blastemas and tumors as examples of non-proliferating and proliferating benign and malignant tissues and their functional characterization.Single cell suspensions from hearts, lungs, repair blastemas and tumors were incubated consecutively with an anti-CD31 antibody and magnetic micro-beads, coupled to a derivative of biotin and streptavidin, respectively. Following magnetic bead separation, CD31-positive ECs were released by biotin-streptavidin competition. In the absence of micro-beads, ECs became adherent to plastic surfaces. ECs from proliferating repair blastemas and tumors were larger and exhibited higher expression densities of CD31, CD105 and CD102 compared to those from non-proliferating normal tissues such as heart and lung. The expression density of CD34 was particularly high in tumor-derived ECs, and that of CD54 and CD144 in ECs of repair blastemas. Functionally, ECs of non-proliferating and proliferating tissues differed in their capacity to form tubes in matrigel and to align under flow conditions.This method provides a powerful tool to generate high yields of viable, primary ECs of different origins. The results suggest that an altered expression of adhesion molecules on ECs in proliferating tissues contribute to loss of EC function that might cause a chaotic tumor vasculature.
EVALuna2:18206